Engineered biosynthesis of cyclotides. Issue 4 (1st October 2020) - Handley, Thomas N. G.; Tan, Hyon-Xhi; Rutledge, Malcolm T.; Brewitz, Hans Henning; Tyndall, Joel D. A.; Kleffmann, Torsten; Butler, Margi I.; Poulter, Russell T. M.; Wilbanks, Sigurd M.
ABSTRACT: A system based on cyanobacterial split inteins, SICLOPPs (Split Intein Circular Ligation of Proteins and Peptides), has been used to synthesise a small natively cyclic plant protein, kalata B1, and cyclised versions of the natively linear therapeutic peptides ziconotide and leconotide. The cyclic versions of these naturally linear peptides include linker sequences between their native termini to allow the correct tertiary structure to form. The native structure of each includes three disulphide bonds characteristic of knottins. Cyclic permutations of leconotide yielded different proportions of correctly spliced product, identifying an optimal splice site and revealing the influence of residues around the splice junction. The rate of splicing was manipulated to facilitate affinity purification prior to intein-mediated removal of the affinity tag.